Penerapan Etika Berbisnis dalam Operasional Usaha Pelaku UMKM Karijawa Permai (Abon) Dikelurahan Karijawa - Kartin Aprianti; Rosa Dwiyanti; M Rian Albar; Kurnia Fajrianti; Miftahul Jannah; Jumyati Jumyati; Resti Ningrum; Efan Iryadin; Zahra Sausan; Muhammad Rizalul Fikri (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2025)
Business ethics is a fundamental aspect in the management of Micro, Small, and Medium Enterprises (MSMEs) to ensure business sustainability and growth. This research discusses the role of business ethics in Karijawa Permai MSMEs, which focuses on building consumer trust, improving reputation, and creating harmonious relationships with stakeholders. Ethical practices, such as honesty in service, regulatory compliance, and social responsibility, help strengthen the position of these MSMEs in the competitive local market. In addition, consistent implementation of business ethics is able to increase employee loyalty and support environmental sustainability. The method offered to partners/MSMEs is in the form of education/socialization using LEAFLET which is carried out door to door. The material provided in the leaflet includes a discussion of (1) The Role of Ethics in Doing Business for MSME Actors, (2) Benefits in Doing Business for MSME Actors (3) The Application of Ethical Principles in Doing Business in Finance, Marketing, Production and Human Resources Activities. The findings show that the effective implementation of business ethics not only improves operational performance, but also has a positive impact on local communities and economies. Thus, business ethics is a strategic element in optimizing the contribution of Karijawa Permai MSMEs to sustainable development. The activity also showed that partners were very enthusiastic in listening and discussing during the activity. In addition, it can provide knowledge about ethics in running a business.